2010
DOI: 10.1111/j.1741-3729.2010.00602.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Experiences of Discrimination and Family Relationship Qualities: The Role of Gender

Abstract: Mothers and fathers in 156 African American families reported on racial discrimination experiences, gendered traits, and warmth and conflict in family relationships. Discrimination was linked with relationship quality, but links differed for mothers and fathers. More expressive parents and less instrumental fathers had more positive relationships in the face of discrimination, but for more instrumental fathers, discrimination-relationship quality links were negative. Findings imply consideration of sociocultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 34 publications
2
61
2
Order By: Relevance
“…In addition to examining internal processes that forecast health functioning, attention also was given to examining ways in which racial discrimination might derail family processes (Riina & McHale, ). Findings in the present study revealed that these demoralizing experiences amplified the negative effects of everyday stressful life events on parents' psychological functioning.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to examining internal processes that forecast health functioning, attention also was given to examining ways in which racial discrimination might derail family processes (Riina & McHale, ). Findings in the present study revealed that these demoralizing experiences amplified the negative effects of everyday stressful life events on parents' psychological functioning.…”
Section: Discussionmentioning
confidence: 99%
“…As such, women may be more likely to provide support to their partners who experience racial discrimination and feel the need to protect them from such social injustices (Cowdery et al., ). Furthermore, women are more likely than men to display and report internalizing symptoms (Banks et al., ), whereas men's responses may present themselves in outward expressions or externalizing symptoms (e.g., Goff, Di Leone, & Kahn, ; Riina & McHale, ). When female partners do not provide this support, men may internalize their stress either in place of or in conjunction with externalizing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that the absence of positive racial messages and messages that make adolescents aware and prepared for the potential of racial discrimination is especially detrimental for youth who experience racial discrimination (Neblett. et al., ; Riina & McHale, ).…”
Section: Multidimensional Model Of Racial Identitymentioning
confidence: 98%